Analysis of the cowpea agroecosystem in West Africa: II. Modelling the interactions between cowpea and the bean flower thrips Megalurothrips sjostedti (Trybom) (Thysanoptera, Thripidae) - Tamo, Manuele; Baumgaertner, J.U.; Gutiérrez, A. (Elsevier, 1993)
The interactions between cowpea and one of its key pests, Megalurothrips sjostedti (Trybom), were evaluated via a simulation model based on three modules building the core of the cowpea growth model, i.e. the time-varying distributed delay, the functional response acquisition function, and the metabolic pool model. The thrips population model was superimposed on the cowpea model in order to evaluate two-trophic level interactions, and the way the interactions are affected by phosphate and water availability in the soil. In addition, the model was used to evaluate the effect of possible biological control candidates on plant-pest interactions.